EVALUATION OF SLOPE STABILITY PROBLEMS: A CASE STUDY OF SLOPE REINFORCEMENT ON EXPANSIVE SOIL FOR THE HIGH-VOLTAGE TRANSMISSION TOWER (SUTT) T80 MALINGPING–BAYAH, SUKABUMI - Bayu Wintoro; Abi Maulana Hakim; Aozora Insan Kamil; Amirah Zakiyyah (LPPM Universitas Negeri Jakarta, 2025)
Expansive soils are highly susceptible to volumetric changes due to moisture fluctuations, which can significantly affect the stability and durability of structures. Therefore, their presence must be carefully considered during the planning and foundation design stages. Survey, field investigations, and lab tests show that soil up to 8 m deep has a plasticity index of 30%–65%. Swelling tests on samples from 1 m–3.5 m depths revealed swelling percentages of 0.545%–0.715% and pressures of 11.7 kPa–12.5 kPa, which are high for near-surface soil. XRD tests identified montmorillonite minerals, known for high activity and shrinkage, contributing to slope cracks and movement. Geotechnical analysis using finite element method shows that slope stability safety factors of 0.84 (static) and 0.62 (earthquake), below required thresholds of 1.5 and 1.1, respectively. The proposed reinforcement includes double-row soldier piles, connected by a capping beam. The slope surface will be graded downstream and reinforced with 1 m thick stone masonry. These measures are expected to increase safety factors to 1.72 (static) and 1.1 (earthquake), meeting safety standards.